국내 목 기능장애에 대한 도수치료 효과의 체계적 문헌고찰 - 이현석; 한진태 (대한정형도수물리치료학회지, 2025)
Background: This study conducted a meta-analysis of domestic randomized controlled trials to evaluate how various manual therapy techniques influence neck disability. Although manual interventions such as Maitland, McKenzie, Mulligan, Kaltenborn, and chiropractic methods are routinely used for non-specific neck pain, their aggregate effects on pain reduction, functional improvement, and cervical range of motion remain unclear. Methods: The five domestic databases were used to implement literature searches independently. A total of 19 out of 925 selected articles were used to analyze, except those overlapped (n=219), those irrelevant to neck disability (n=364), those consisting of the abstract and presentation notes alone (n=19), those without manual therapy intervention or dealing with other types of intervention (n=298), and those making it possible to apply the same kind of intervention to other sites (n=6). The intervention followed the guidelines presented as five types of manual therapy, and used the risk of bias in Cochrane library to assess the quality of the literature. Results: An uncertain risk was ‘random sequence generation' in three articles and ‘non-public grouping' in fifteen articles. ‘Blinding of the subjects and the researcher' was mentioned in only one article, and no article mentioned ‘blinding for result assessment'. Seven articles were at high risk of ‘incomplete results,' and one was at high risk of ‘selective result report'. Conclusion: Current domestic evidence indicates that manual therapy methods significantly alleviate pain, decrease neck-related disability, and enhance cervical mobility in patients with neck dysfunction. To strengthen these findings, future trials should employ rigorous blinding, standardized intervention protocols, and larger samples. Integrating manual therapy into multidisciplinary rehabilitation programs is supported by this meta-analysis as an effective approach for managing neck disability.